EFEKTIVITAS PEMANFAATAN TEKNOLOGI DALAM MENDUKUNG PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Sovia Harahap; Adi Zulkifli Boangmanalu; Chairunnisa; Amelia Putri; Hadis Purba (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2024)
This research aims to analyze the effectiveness of using technology in supporting Islamic Religious Education learning, therefore the aim of this research focuses on two studies, namely: the effectiveness of using technology in PAI learning and factors inhibiting the effectiveness of using technology in PAI learning. This type of research uses a qualitative approach. The approach used is a descriptive study. In qualitative approach research, the data is in the form of sentences or narratives obtained through qualitative data collection techniques. The research results explain that educational technology has a very important role in the learning process. With the existence of educational technology, it will certainly make learning activities easier, where educators will find it easier to transfer information to students and of course students will also more easily understand the information conveyed by educators. Educators need to understand how to apply educational technology well so that educational technology can be effectively applied in the learning process. Especially in Islamic religious education learning, educational technology must really be considered so that the use of technology can be in line with learning objectives that are based on the Al-Qur'an and Sunnah. Keywords : Effectiveness, Technology, Islamic Religious Education.